Nextcloud Based Personal Cloud Storage Implementation on Raspberry-Pi 4 for Lightweight Cloud Infrastructure - Ahmad Asep Suhendi; Noprianto Noprianto; Ragil Nur Iman; Syifaurachman Syifaurachman (Progresif: Jurnal Ilmiah Komputer, 2026)
Cloud computing has emerged as a prevalent technique for data storage and management via internet-based platforms, eliminating the need for local storage devices. Nonetheless, public cloud services like Google Drive and Dropbox have issues related to data privacy, security, and user control over the foundational infrastructure. This study advocates for the deployment of a private cloud storage system utilizing Nextcloud on a Raspberry Pi 4 as a streamlined and economical infrastructure option. The Raspberry Pi is chosen for its compact dimensions, little power usage, and cost-effectiveness relative to traditional servers. The system is constructed on Ubuntu Server, utilizing Apache as the web server, MySQL as the database management system, and PHP to facilitate the Nextcloud application. The research process encompasses system requirements analysis, system design, implementation, and thorough testing. The findings indicate that the system effectively delivers critical cloud storage capabilities, encompassing file upload, download, sharing, data synchronization, and user access management. The performance assessment reveals that the system functions stably, responsively, and reliably for small to medium-scale storage requirements, while ensuring a sufficient degree of security.Keywords: Cloud computing; Cloud storage; Raspberry-pi; Nextcloud; Lightweight cloud infrastructure;AbstrakCloud computing menjadi teknologi yang banyak diadopsi untuk penyimpanan dan pengelolaan data melalui internet tanpa bergantung pada perangkat lokal. Namun, layanan cloud publik seperti Google Drive dan Dropbox menimbulkan kekhawatiran terkait privasi, keamanan, serta kendali pengguna terhadap data dan infrastruktur. Penelitian ini mengusulkan implementasi sistem cloud pribadi berbasis Nextcloud pada Raspberry Pi 4 sebagai solusi infrastruktur ringan dan berbiaya rendah. Raspberry Pi dipilih karena ukurannya ringkas, hemat daya, serta ekonomis dibandingkan server konvensional. Sistem dibangun menggunakan Ubuntu Server dengan Apache sebagai web server, MySQL sebagai database, serta PHP untuk mendukung aplikasi. Metodologi penelitian meliputi analisis kebutuhan, perancangan sistem, implementasi, dan pengujian sistem secara menyeluruh dan terstruktur. Hasil menunjukkan sistem mampu menyediakan fitur unggah, unduh, berbagi file, sinkronisasi data, serta manajemen akses pengguna secara efektif dan efisien. Pengujian kinerja menunjukkan sistem berjalan stabil, responsif, dan andal untuk kebutuhan penyimpanan skala kecil hingga menengah secara optimal dan berkelanjutan dengan tingkat keamanan yang memadai.Kata kunci: Komputasi awan; Penyimpanan awan; Raspberry-pi; Nextcloud; Infrastruktur awan ringan